Teacher education and inclusive didactics: listening, relationship and participation at school - Garaffo, Teresa (Formazione & insegnamento, 2017)
The article describes an experience of teacher education that aimed to improve the ability to guide a class group in its complexity. This is achieved through the recognition and observation of specific difficulties of single pupils or subsets of the group. It also deals with the ability to design strategies apt to prevent educational failure and limit causes of school discomfort. It is not possible to have inclusive schools without improving teacher professionalism.